Discussion on the Structural Modification and Anti-tumor Activity of Flavonoids - Zhou, Zhu-Gui; Li, Dong-Dong; Chen, Ying; Chen, Xi; Man, Ruo-Jun (Current Topics in Medicinal Chemistry, 2022)
Flavonoids are secondary metabolites of plants. In general#140;most flavonoids are combined with glucosides and have extremely complex molecular structures. In nature, these flavonoids have a variety of biological activities, such as anti-oxidation#140;anti-virus, anti-tumor, scavenging free radicals, etc.; however#140;due to poor solubility and stability of flavonoids#140;their bioavailability is limited. The drug design method is used to modify the structure of flavonoids to give them special properties. At present, flavonoids have shown broad application prospects in treating tumors, inhibiting proliferation, migration, invasion, angiogenesis, and multi-drug resistance of tumors and have become a research hotspot.
Keywords: Flavonoids